Functionalized textiles with PUU/limonene microcapsules: effect of finishing methods on fragrance release - Silva, M. (2017)
The majority of the commercially available microencapsulated fragrance systems with interest for textile applications are based on phenol–formaldehyde/melamine–formaldehyde resins. Recognized human health problems concerning formaldehyde emissions led to the use of poly(urethane–urea) (PUU) systems. In this work, fabrics were impregnated with PUU microcapsules containing limonene produced by interfacial polymerization. To aid the microcapsule impregnation, a specific binder was used followed by a drying and thermofixation process. The textiles were then subjected to abrasion and dry cleaning tests. Fragrance release was analysed for different binder to microcapsule ratios. SEM images of the impregnated samples indicate good adhesion of the microcapsules to the fabric fibres, but some capsule breakage was observed. Fragrance release tests were followed by GC–FID–HS and showed good resistance to abrasion tests with 30% of the initial limonene detected after 9000 abrasion cycles. A lower resistance was observed for the dry cleaning tests, although 20% of the limonene was still present after five dry cleaning cycles.